Nonlinear dynamic analysis of a new antibacklash gear mechanism design for reducing dynamic transmission error - Besharati, S.R.; Dabbagh, V.; Amini, H.; Sarhan, A.A.D.; Akbari, J. (Asme, Two Park Ave, New York, Ny 10016-5990 Usa, 2015)
In this study, a new antibacklash gear mechanism design comprising three pinions and a rack is introduced. This mechanism offers several advantages compared to conventional antibacklash mechanisms, such as lower transmission error as well as lower required preload. Nonlinear dynamic modeling of this mechanism is developed to acquire insight into its dynamic behavior. It is observed that the amount of preload required to diminish the backlash depends on the applied input torque and nature of periodic mesh stiffness. Then, an attempt is made to obtain an approximate relation to find the minimum requiring preload to preserve the system's antibacklash property and reduce friction and wear on the gear teeth. The mesh stiffness of the mated gears, rack, and pinion is achieved via finite element method. Assuming that all teeth are rigid and static transmission error is negligible, dynamic transmission error (DTE) would be zero for every input torque, which is a unique trait, not yet proposed in previous research.